What can rats tell us about neuropathic pain? : critical evaluation of behavioral tests used in rodent pain models - Sapunar, Damir (Array, 2009)
Animal models are a necessity in the study of neuropathic pain, and much of what we know about pain comes from studies in mice and rats. However, very few basic discoveries have been translated so far from rodent models into effective pain therapy. This review presents the most important rat models used in basic pain research, discusses their limitations and recommends better use of these models in future studies. A critical review of existing literature on rat models of neuropathic pain is made. Different models are compared and their contribution to pain research presented.